TRANSFORMATIONAL LEADERSHIP AND WORK ENGAGEMENT: MEDIATING ROLE OF PSYCHOLOGICAL EMPOWERMENT - Ayu Dina, Dyah; Tjahjono, Heru Kurnianto (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: Work engagement has gained significant attention over the past two decades, particularly within the evolving business environment of the 21st century. This research aims to examine the impact of transformational leadership on work engagement, with psychological empowerment as the mediating factor. Methods: This research is a quantitative study using primary data obtained through a questionnaire survey of employees in one of the Indonesian private companies active in the field of distribution of biotechnology research laboratory equipment. The measurement is done using the Likert Scale and data analysis is done with the help of the PLS-SEM tool. Results: The research findings indicate that transformational leadership positively influences work engagement, with psychological empowerment mediating the relationship between transformational leadership and work engagement. These findings suggest that leaders who adopt transformational leadership styles can enhance work engagement through psychological empowerment. Conclusion and suggestion: This research provides valuable insights for organizations that want to enhance the work engagement of their employees, especially in situations of organizational restructuring. In addition, the study also emphasizes the importance of job resources in helping to create a working environment that supports high work engagement.